2016
DOI: 10.20869/auditf/2016/133/65
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Auditors’ Rotation on the Accounting Quality in the Case of Romanian Listed Companies under the Transition to IFRS

Abstract: In assuring the quality of the financial information issued by the listed companies, the role of the financial auditor is to express his own opinion regarding the compliance of the financial statements with a financial reporting framework. In order for this opinion to be a reliable one, the auditor has to develop it considering the specific requirements of competence, ethic judgment and professional ethics. Meeting these requirements supposes significant efforts from the auditors, and also from the professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Furthermore, Popa et al [52] and Robu et al [53] highlight auditors' professional judgment, ethical judgment as well as professional ethics as key elements in their decision-making process. Moreover, the authors of [53] showed that an auditor's rotation can significantly contribute to a shift in the relevance degree of the value of the data disclosed by Romanian companies that are quoted on the BVB.…”
Section: Audit Risk Materiality and The Professional Judgment Of Thementioning
confidence: 99%
“…Furthermore, Popa et al [52] and Robu et al [53] highlight auditors' professional judgment, ethical judgment as well as professional ethics as key elements in their decision-making process. Moreover, the authors of [53] showed that an auditor's rotation can significantly contribute to a shift in the relevance degree of the value of the data disclosed by Romanian companies that are quoted on the BVB.…”
Section: Audit Risk Materiality and The Professional Judgment Of Thementioning
confidence: 99%
“…In order to improve the quality of estimated results and eliminate the influence of scale effects (Robu et al, 2016), in equation 1, we use financial ratios as shown below:…”
Section: Models and Data Sourcementioning
confidence: 99%
“…In this regard, Robu et al (2016) focused on 64 Romanian companies listed on the Bucharest Stock Exchange between 2006 and 2014. They found that the auditor's rotation significantly contributes to the change of the value relevance degree.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…This signal should convince them that an independent auditor analyses, reviews, and develops an auditing opinion asserting the relevance and the faithfulness of the audit firm's financial statements for external users. Thanks to audit firm rotation, investors should perceive accounting amounts to be value relevant (Robu et al, 2016). Key partner rotation also acts as a signal.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation